Resiliencia en estudiantes adolescentes de una institución educativa de una zona urbano-marginal durante el covid-19: Resilience in adolescent students form an educational institution in an urban-marginal area during covid-19 - Cunias Rodríguez, Marita Yannyna (2021)
This research aimed to measure the level of resilience in adolescents in an educational institution located in an urban-marginal area during the Covid 19 pandemic, with the purpose of identifying the levels of emotional competence and self-acceptance during the health emergency, by applying the Wagnild and Youn Resilience Scale to 143 adolescents. The research method used was the descriptive one, with a nonexperimental design. The results indicate that the students are capable of adapting positively to adverse contexts, managing to develop their emotional competence, likewise, they possess the ability to build their own identity and accept themselves, essential factors for the development of an adequate self-esteem and the fulfillment of long term goals, for which they have sufficient resources to face their future.